Perception of Effective Multicultural Leadership: A Qualitative Study in Western Java - Eri Radityawara Hidayat; I Gede Sumertha; Cornelia Istiani (Fakultas Psikologi Universitas Indonesia dan Ikatan Psikologi Sosial-HIMPSI, 2020)
With the rise of ethno-religious conflicts in Indonesia, this qualitative study aims to find the criteria for effective leadership in Indonesia’s multicultural setting. A total of 8 informants were interviewed and 14 others participated in a two Focus Group Discussions. Results showed that factors related to effective multicultural leadership in handling etno-religious conflicts were personal attributes, behavioral competencies, and experience related to the diversity. One significant finding of this research which is different from other researches in secular Western settings is the role of religiousity in enhancing leadership effectiveness for handling etno-religious conflicts. This result showed the need for further researches on leadership effectiveness in various contexts in non Western cultures.